Involvement of Tunisian General Practitioners in the Management of Patients at Risk of Infective Endocarditis: A Cross-Sectional Study - Malek Lagha; Mehdi Khemiss; Ines Kallel; Asma Araissia; Chems Belkhir; Saida Sahtout; Sana Bagga (International Journal of Dentistry)
Objectives. This work aimed to estimate the knowledge and practice of general dentists in the governorate of Manouba regarding the management of patients at risk of infective endocarditis. Materials and Methods. A survey involving private sector general dentists in the governorate of Manouba was performed. It contained 21 questions, and it was addressed to 111 dentists. Only 82 dentists responded. To carry out the descriptive study, we used the SPSS software version 21.0. Results. Our results proved the lack of knowledge among dentists in the governorate of Manouba with regard to the management of patients at risk of infective endocarditis. An overestimation of the risk and an overprescription of antibiotic were found in order to ensure an over-protection for the patients as well as the dentist. In fact, 85.4% of these dentists prescribed antibiotic prophylaxis for the two groups of patients (high risk and moderate risk). Only 9.8% followed the right modality of antibiotic prophylaxis prescription; 4.9% of the dentists prescribed antibiotic only 1 hour before the act and 4.9% of them prescribed antibiotic 1 hour before the act and continued the treatment in case of the presence of an infectious site. Conclusion. A discrepancy towards an over-estimation of risk and overprescription of antibiotic was found between the recommendations and real practice. Similar studies in the other governorates of Tunisia are recommended in order to better understand the problem.